2021
DOI: 10.5812/jjm.117884
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polymerase Chain Reaction in Diphtheria Laboratory Examination: A Field Need

Abstract: Background: Indonesia is one of the five countries with the highest number of diphtheria cases worldwide. Diphtheria is caused by the toxigenic strains Corynebacterium diphtheriae, C. ulcerans, and C. pseudotuberculosis. The diphtheria-causing bacteria can be identified using conventional and molecular methods, including polymerase chain reaction (PCR) assay. We used the PCR assay as additional testing, because in island countries like Indonesia, specimen transport is a serious challenge to maintaining bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Unlike our previous study (13), we did not identify the NTTB strains to reduce the cost in this study because of the high cost of the PCR probe. Furthermore, previous studies documented that NTTB strains were never observed in diphtheria samples in Indonesia (4,10,13). The NTTB strain originated in Indonesia was isolated from the non-diphtheria sample (21).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Unlike our previous study (13), we did not identify the NTTB strains to reduce the cost in this study because of the high cost of the PCR probe. Furthermore, previous studies documented that NTTB strains were never observed in diphtheria samples in Indonesia (4,10,13). The NTTB strain originated in Indonesia was isolated from the non-diphtheria sample (21).…”
Section: Discussionmentioning
confidence: 95%
“…Although the diagnosis and treatment of diphtheria are based on clinical manifestation, some cases are mild and atypical. Laboratory tests are needed to rule out a differential diagnosis (9,10). The fast and accurate laboratory tests help prevent the spread of diphtheria-causing bacteria and provide case management as early as possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation